Event-triggered asynchronous periodic distributed secondary control of microgrids under DoS attacks. Issue 17 (November 2022) - Li, Zengwei; Che, Weiwei
Abstract: A novel distributed secondary voltage and frequency control strategy is proposed with the Zeno-free event-triggered scheme for an island alternating current (AC) microgrid under Denial-of-Service (DoS) attacks. A DoS attack compensation mechanism and an event-triggered mechanism on the basis of the checking scheme are developed. Then, a secure event-checked based event-triggered secondary control method is explored to guarantee the tracking performance of the microgrid under DoS attacks. Further, some linear matrix inequalities (LMIs)-based sufficient conditions are derived to design the controller. What's more, the proposed asynchronous periodic triggering method can efficiently save communication resources and further reduce the update number of the controller. Finally, the efficiency of this work is verified by an islanded AC microgrid with comparisons.